Molecular characterization ofStaphylococcus argenteusin Myanmar: identification of novel genotypes/clusters in staphylocoagulase, protein A, alpha‐haemolysin and other virulence factors. Issue 1 (January 2019) - Aung, Meiji Soe; San, Thida; San, Nilar; Oo, Win Mar; Ko, Phyoe May; Thet, Khin Thet; Urushibara, Noriko; Kawaguchiya, Mitsuyo; Sumi, Ayako; Kobayashi, Nobumichi
Abstract : Purpose. : Staphylococcus argenteus is a novel emerging species of coagulase‐positive staphylococcus that is genetically closely related to Staphylococcus aureus . To elucidate the molecular differences in the virulence factors (staphylocoagulase, protein A, alpha‐haemolysin, enterotoxin‐like toxin and staphylokinase) between these staphylococcal species, S. argenteus that had recently been isolated in Myanmar (five nasal isolates and four clinical isolates) were analysed. Methodology. : The nucleotide sequences of the virulence factors were determined by PCR and direct sequencing, followed by phylogenetic analysis by mega6 and multiple alignment by clustalw using the published sequence data for S. aureus and S. argenteus . Results. : Six S. argenteus isolates belonged to MLST sequence type (ST) 2250, while others belonged to ST4625, ST2198 and ST2854. The novel staphylocoagulase ( coa ) genotype XIV and the novel coa ‐XI subtype (XId) were identified in an ST2198 isolate and all other isolates, respectively. Among the S. argenteus isolates, the protein A and alpha‐haemolysin genes showed high sequence identity (96–98 % and >99 %, respectively), while lower identity was observed between S. argenteus and S. aureus (88–91 % and 86 %, respectively), with both species showing phylogenetically distinct clusters. Similar findings were found for the staphylococcal enterotoxin (SE)‐like toxin genes selw, selx and sely . In contrast, the staphylokinase genes were almost identical between these two species. All of the coa ‐XId isolates had a CRISPR/Cas locus at the site of orfX without having SCC mec, whereas an ST2198 isolate lacked this locus. Conclusion. : The primary virulence factors (staphylocoagulase, protein A andalpha‐haemolysin) as well as the SE‐like toxins of S. argenteus were genetically discriminated from those of S. aureus, revealing the presence of the novel coa ‐type/subtype ( coa ‐IXd, XIV) in S. argenteus .